Megadiverse Ecuador: a review of Mysmenopsis (Araneae, Mysmenidae) of Ecuador, with the description of twenty-one new kleptoparasitic spider species - Dupérré, Nadine; Tapia, Elicio (Zootaxa, 2020)
The spider family Mysmenidae includes two genera in which kleptoparasitic species are known to occur, Isela and Mysmenopsis. Mysmenopsis is the most speciose with 31 species described so far. Herein, we describe twenty-one new species from Ecuador: M. alvaroi n. sp., M. amazonica n. sp., M. angamarca n. sp., M. awa n. sp., M. baerti n. sp., M. bartolozzii n. sp., M. choco n. sp., M. cube n. sp., M. corazon n. sp., M. guanza n. sp., M. guayaca n. sp., M. hunachi n. sp., M. junin n. sp., M. lasrocas n. sp., M. lloa n. sp., M. otokiki n. sp., M. pululahua n. sp., M. salazarae n. sp., M. shushufindi n. sp., M. tepuy n. sp. and M. tungurahua n. sp. We report for the first time the presence of four species of Mysmenopsis in the web of a Lycosidae, namely M. salazarae n. sp., M. shushufindi n. sp., M. bartolozzii n. sp. and M. amazonica n. sp. All new species described here were collected in spider webs either from the family Dipluridae (Linothele) or Lycosidae (Aglaoctenus) and therefore are assumed to be kleptoparasitic. New locality records are presented for M. otonga, M. fernandoi, M. atahualpa and M. penai, the female of M. penai is described for the first time. Maps of all Ecuadorian species are presented, kleptoparasitism, morphological characters and distribution of Mysmenopsis species are discussed.